A core-shell structured alginate hydrogel beads with tunable thickness of carboxymethyl cellulose coating for pH responsive drug delivery. Issue 6 (13th April 2021) - Yan, Mingzhu; Chen, Tiantian; Zhang, Shuping; Lu, Ting; Sun, Ximeng
Abstract: pH-responsive core-shell structured composite hydrogel beads, composed of a alginate (ALG) core coated with carboxymethyl cellulose (CMC) shell (ALG@CMC), were prepared by using in-situ gel preparation technology as a drug delivery system. An anti-inflammatory drug, indomethacin was loaded into the formed hydrogels as a model drug. The resulting gel samples were characterized by Fourier transforms infrared (FTIR) spectroscopy, thermo-gravimetric (TG) analysis, and scanning electron microscopy (SEM). The mechanical stability of all samples in phosphate buffered solution (PBS, pH 7.4) was approximately measured through oscillation experiments. Swelling and controlled drug release behaviors of ALG@CMC beads compared with ALG were studied in simulating gastric fluid of pH 1.2 or intestinal fluid of pH 7.4 at 37 °C. Oscillation experiments proved that the mechanical stability of ALG@CMC beads could be significantly improved by the CMC shell layer. The swelling and drug release behaviors revealed that the swelling and drug release rate of ALG@CMC beads were obviously slower than that of simple-ALG and both have significant pH responsiveness. The cumulative drug release from ALG, ALG@CMC-1, ALG@CMC-2 and ALG@CMC-3 was about 100%, 67%, 46% and 37% in simulated intestinal fluid of pH 7.4, respectively, while the drug release reached only about 2.0% in simulating gastric fluid of pH 1.2 within 720 min. These developed materials could potentially be employed as a pH-responsive drug delivery device in vivo .